The Relationship of Stroke Incidents With Clients’ Quality of Life - Savira, Untari Arda; Widiyawati, Wiwik; Zuhroh, Diah Fauzia; Sari, Diah Jerita Eka (Universitas Muhammadiyah Gresik, 2024)
Stroke is a condition where the blood supply to the brain is disrupted or reduced due to blockage (ischemic stroke) or rupture of blood vessels (hemorrhagic stroke). Stroke can cause physical disability, this can affect psychological, emotional, cognitive and even social conditions. So post-stroke sufferers will experience changes in their quality of life. The aim of this research is to analyze the relationship between the incidence of stroke and the quality of life of clients at RSUD Ibnu Sina Gresik. This research uses an observational research design with a cross sectional approach. The total population was 451 clients, 82 samples were studied using consecutive sampling techniques. The instrument used in the research was the WHOQOL-BREF questionnaire and then the collected data was analyzed using the SPSS Chi-Square Test. Almost all of the stroke clients who were controlled at the neurological clinic at Ibnu Sina Gresik Regional Hospital experienced a stroke once, 62 (75.6%) of the clients and almost all of the quality of life of stroke clients who were controlled at the neurological clinic at Ibnu Sina Gresik Regional Hospital experienced a fairly good quality of life. 66 (80.5%) clients. The results of the collected data were then analyzed to obtain P = 0.624 > 0.05, so H1 was rejected and H0 was accepted. In conclusion, there is no relationship between the incidence of stroke and the quality of life of clients at Ibnu Sina Gresik Regional Hospital. Keywords : Stroke, Quality of Life, Clients